Talking Pillow - Ball, Angela, 1952- (Pitt poetry series., 2017)
Talking Pillow celebrates love as amazement, sustenance, and the progenitor of scarce-believable loss. The book centers around the sudden death of the author's long-time partner and travels outward to events in the world at large. Imagining themselves into multiple times, places, and lives, the poems comically explore the possibilities of attachment between people and the absurdity of death's sudden intrusion. Antic and often funny, these poems converse with all that we care about, fear, and fail to understand.